Resilience in the post-welfare inner city : voluntary sector geographies in London, Los Angeles and Sydney / Geoffrey DeVerteuil. - DeVerteuil, Geoffrey (Policy Press, 2015)
Moving beyond theoretical notions of 'resilience', this is the first book to offer a conceptual and empirical approach to exploring and comparing the process of resilience across service 'hubs' in three complex but different global inner-city regions: London, Los Angeles and Sydney.